DEVELOPMENT OF THE ACTIVE LEARNING-ORIENTED STUDENT WORKSHEETS IN PLANT NUTRITION CONSEPTS - ZAHROTUS SAADAH (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
The objectives of this research are to 1) provide student worksheets with active learning-oriented that are feasible, 2) describe the feasibility of student worksheets the theoretically based on experts and practitioner of biology review results, 3) describe the empirical feasibility of the student responses to the worksheets on the subject of obtaining plant nutrition system. This type of research is student worksheets development with active learning-oriented. The development used FourD model (4D). Student worksheet's feasibility data were obtained from result of review of the worksheets by experts and practitioner of biology, and student responses to student worksheets. Data obtained were analized quantitatively and descriptively. The results show that 1) student worksheets has been the resulting feasible active learning -oriented is used, 2) student worksheets got a value of 3,48 with excellent category. It can be said that they are feasible theoretically based on experts and practitioner of biology review, 3) the result of the student responses to the worksheets got a positive value of 94%. Keyword: student worksheet development, active learning, plant nutrition consepts.